A New Vision for Evaluating the Quality of E-Commerce Websites - Rababah, Osama M.; Al-Shboul, Muhannad; Al-Sayyed, Rizik (International Journal of Advanced Corporate Learning (iJAC), 2011)
Quality has been established as a key factor in ensuring the success of E-commerce in attracting and retaining customers. To help in this, numerous software metrics and website quality models have been developed, with a correspondingly large literature. We provide a critical review of this literature and the state-of-the-art. Most of the wide ranges of E-commerce website evaluation models give emphasis on the web applications of the system, using techniques like feature inspection and collecting data about end-usersâ?? opinion by questionnaires. However, this is in conflict with two fundamental pragmatic aspects of current websites. Web technologies evolve extremely fast, enabling sophisticated tools to be deployed and complex interactions to take place. Secondly, the life cycle of a website is also extremely fast: maintenance of a website is performed at a rate that is higher than that of other software products because of market pressure and lack of distribution barriers.